2000
DOI: 10.1111/j.1532-5415.2000.tb02594.x
|View full text |Cite
|
Sign up to set email alerts
|

Physician Orders for Life‐Sustaining Treatment (POLST): Outcomes in a PACE Program

Abstract: POLST completion in ElderPlace exceeds reported advance directive rates. Care matched POLST instructions for CPR, antibiotics, IV fluids, and feeding tubes more consistently than previously reported for advance directive instructions. Medical intervention level was consistent with POLST instructions for less than half the participants, however. We conclude that the POLST is effective for limiting the use of some life-sustaining interventions, but that the factors that lead physicians to deviate from patients' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 21 publications
2
94
0
1
Order By: Relevance
“…This finding stands in contrast to a number of studies concluding that preferences fail to determine the receipt of specific medical interventions. 12,16,17 This difference in conclusions results in part from the conceptualization of end-oflife care in terms of pathways of care. These pathways were developed with the recognition that specific interventions can be used with different goals regarding the outcomes of care and attempt to capture how well patients' care goals are met at the end of life.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This finding stands in contrast to a number of studies concluding that preferences fail to determine the receipt of specific medical interventions. 12,16,17 This difference in conclusions results in part from the conceptualization of end-oflife care in terms of pathways of care. These pathways were developed with the recognition that specific interventions can be used with different goals regarding the outcomes of care and attempt to capture how well patients' care goals are met at the end of life.…”
Section: Discussionmentioning
confidence: 94%
“…8 Studies prospectively evaluating patients' preferences and their relationship to the care patients receive have focused on the site of death [9][10][11] or on the receipt of specific interventions. [12][13][14][15][16][17] Determining whether patients' preferences for end-of-life care have been met requires an examination of whether the care that they receive is consistent with their goals or, in other words, whether the treatment will provide the outcomes that patients desire. This is because patients' preferences are shaped by the probable outcomes of treatment rather than the specific intervention itself.…”
Section: Introductionmentioning
confidence: 99%
“…In a smaller, retrospective study of 54 frail elderly adults enrolled in a capitated senior health program, only 39% (21 of 54) had their POLST orders followed consistently. 3 A study of hospice patients found a high rate of consistency between treatments provided and POLST orders. 4 A recent retrospective study 5 compared the use of POLST with the standard approach of writing medical orders for 1711 long-term care residents in three states.…”
mentioning
confidence: 99%
“…37 Tracking this innovation as a natural experiment, investigators have found evidence that POLST is effective to facilitate care consistent with preferences for older patients in nursing homes, PACE, and hospice. [38][39][40] Can Interventions Improve the Quality of Decision Making?…”
Section: -31mentioning
confidence: 99%